The sympatry of closely related species of ixodid ticks and its possible role in the parasitic systems of natural foci of transmissible diseases - Filippova, N A (Parazitologija, 1999)
Sympatry of the following pairs (or groups) of closely related species in the territory of the former Soviet Union amd some neighbouring countries has been revealed as a result of a revision of the fam. Ixodidae: I. persulcatus-I. ricinus, I. persulcatus-I. pavlovskyi, I. crenulatus-I. kaiseri, Dermacentor marginatus-D. silvarum-D. ushakovae, D. ushakovae-D. niveus, D. pavlovskyi-D. montanus, Rhipicephalus turanicus-R. sanguineus, R. turanicus-R. rossicus, R. turanicus-R. pumilio, R. rossicus-R. pumilio. Biotope and host relationships of sympatric species, as well as seasons of parasitizing have been described on the basis of the field researches conducted by the author, the collections of the Zoological Institute, Russian Academy of Sciences, and the publications substantiated by collection materials studied by the author. Hypothetic ways of the paleogenesis of each sympatric area and geological age have been considered. The recent sympatric area for I. persulcatus-I. ricinus (fig. 1) is of Holocene age (max. 8.000-10.000 years). During that period approximately 1600-2000 sympatric generations could have been realized. Some recent sympatric areas (I. persulcatus-I. pavlovskyi, and some species of other genera) are of Pleistocene and even Pliocene age (2-10 million years). In these areas the number of realized sympatric generations must have been much higher. Several variants of joint simultaneous and successive feeding on one and the same host individual have been established for stages of life cycles of sympatric species of ticks. Contacts of this kind could have created canals for multiple oscillatory exchange of pathogenic taxa (species, genospecies, strains) in a few or many thousands of sympatric generations of closely related vectors. Thus, the same taxon of a pathogen may be subject to different influence of ixodid vectors in sympatric area and in the area of separate habitat of close species of vectors.